Pengaruh Rasio Keuangan Terhadap Kinerja Keuangan Pada PT. Goto Setelah Melakukan Marger Periode 2022-2023 - Rahayu, Nur Widya; Armin, Rini; Verlandes, Yuliasnita (PT. Kreasi Karya Majakata, 2024)
The merger between Tokopedia and Gojek in 2021 created GoTo Group, a holding company that controls various business units including Gojek, Tokopedia, GoPay, and GoTo Financial. Prior to this merger, Tokopedia and Gojek were two separate business entities that had operated independently in Indonesia. However, these two companies have the same vision and mission, so these two companies decided to merge to become PT GoTo in the hope of getting high profitability. The data used is PT Goto's annual financial report for the 2022-2023 period. The independent variables in this research include liquidity ratios, profitability, leverage and activity, while the dependent variable is financial performance as measured by ROA (Return on Assets) and ROE (Return on Equity). The analytical method used is regression to test the relationship between these variables. It is hoped that the results of this research will provide a clear picture of the impact of mergers on company financial performance. It is hoped that the practical implications of this research can help PT. Goto management in making better strategic decisions in the future.